Effect of multiple conductions on basic parameters in linear and saturation regions for a MIS-HEMT from 450 K down to 200 K - Perina, Welder F.; Martino, Joao A.; Simoen, Eddy; Peralagu, Uthayasankaran; Collaert, Nadine; Agopian, Paula G. D. [UNESP] (Journal of Integrated Circuits and Systems, 2024)
In this work, the effect of multiple conductions on the basic parameters in linear and saturation regions of a GaN based Metal-Insulator-Semiconductor High Electron Mobility Transistor (MIS-HEMT), when operating in a temperature range from 450 K down to 200 K, is evaluated experimentally. The threshold voltage behavior suggests that the HEMT conduction is dominating the device for low temperatures, while the MOS conduction is the dominant one for high temperatures. It is also shown that the presence of a high gate leakage current is degrading the switching efficiency and the ION/IOFF ratio of the device. The device presents a minimum Drain Induced Barrier Lowering (DIBL) of 27 mV/V (at 300 K) and the maximum of 62 mV/V (at 450 K).
Keywords: basic parameters; GaN; heterostructure; linear; MIS-HEMT; saturation; temperature; threshold voltage